Political Rhetoric of East Java’s Governor and Deputy Governor Candidates - Anang Sujoko (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2021)
Public debate is one of the stages in a General Election determined by the Commission of Election (KPU) to present the vision, missions, ideas, and programs of prospective leaders to the public. Political rhetoric is a specific study on how political actors try to persuade or attract public voters’ sympathy. This study aimed to reveal Governor and Deputy Governor candidates’ rhetoric in the 2018 East Java Public Debate, using an interpretative qualitative research method with political rhetorical analysis from Finlayson. This study used documentation techniques of the broadcasted recording of Public Debate I, II, and III by TVRI Surabaya and JTV Surabaya for the data collection. The study results indicated that the two candidates for Governor and Deputy Governor of East Java in 2018 had their respective political rhetoric strategies in persuading prospective voters when the Public Debate took place, started from the context contestation; candidate character in rhetoric; contestation perception; and ideological contestation.